Optimizing Extension Communication in The Prevention of Sexual Harrasment in Higher Education Institutions (Systematic Literature Review) - Ritonga, Aulia Rahma; Thamrin, Muhammad Husni; Nur'aini (Talenta Publisher, 2024)
This study aims to optimize communication strategies for preventing sexual harassment in higher education institutions. Amid rising incidents of sexual harassment that threaten the safety and well-being of students, especially women aged 18-24, there is an urgent need for more effective interventions. Employing a descriptive qualitative approach, this research analyzes data from various scientific publications, official documents, and journals using content analysis techniques to identify main themes and categorize relevant information. The findings suggest that effective counseling communication strategies are crucial in preventing sexual harassment within higher education institutions. The study highlights the importance of education and awareness, development of interpersonal communication skills, provision of support resources, specialized training for facilitators, integration of a comprehensive sexual education curriculum, and the use of media and technology in counseling. These approaches aim to deepen understanding, enhance support for victims, and develop inclusive and effective prevention strategies. The discussion emphasizes the need for adapting communication strategies to match the cultural context and policies of each institution to enhance their effectiveness. Recommendations from this research include a holistic integration of approaches focusing on training, advocacy, and clear policies, as well as ongoing evaluation to assess and improve existing strategies, ensuring their effectiveness in preventing sexual harassment in university environments.